Effect of strontium substituted ß‐TCP associated to mesenchymal stem cells from bone marrow and adipose tissue on spinal fusion in healthy and ovariectomized rat. Issue 11 (4th April 2019) - Salamanna, Francesca; Giavaresi, Gianluca; Contartese, Deyanira; Bigi, Adriana; Boanini, Elisa; Parrilli, Annapaola; Lolli, Roberta; Gasbarrini, Alessandro; Barbanti Brodano, Giovanni; Fini, Milena
Abstract: Despite alternatives to autogenous bone graft for spinal fusion have been investigated, it has been shown that osteoconductive materials alone do not give a rate of fusion comparable with autogenous bone. This study analyzed a strontium substituted ß‐tricalcium phosphate (Sr‐ßTCP) associated with syngeneic, unexpanded, and undifferentiated mesenchymal stem cells from bone marrow (BMSC) or adipose tissue (ADSC) as a new tissue engineering approach for spinal fusion procedures. A posterolateral fusion was performed in 15 ovariectomized (OVX) and 15 sham‐operated (SHAM) Inbred rats. Both SHAM and OVX animals were divided into three groups: Sr‐ßTCP, Sr‐ßTCP + BMCSs, and Sr‐ßTCP + ADSCs. Animals were euthanized 8 weeks after surgery and the spines evaluated by manual palpation, micro‐CT, and histology. For both SHAM and OVX animals, the fusion tissue in the Sr‐ßTCP + BMSCs group was more solid. This effect was significantly higher in OVX animals by comparing the Sr‐ßTCP + BMCSs group with Sr‐ßTCP + ADSCs. Radiographical score, based on micro‐CT 2D image, highlighted that the Sr‐ßTCP + BMCSs group presented a similar fusion to Sr‐ßTCP and higher than Sr‐ßTCP + ADSCs in both SHAM and OVX animals. Micro‐CT 3D parameters did not show significant differences among groups. Histological score showed significantly higher fusion in Sr‐ßTCP + BMSCs group than Sr‐ßTCP and Sr‐ßTCP + ADSCs, for both SHAM and OVX animals. In conclusion, our results suggest that addition of BMSCs to a Sr‐ßTCP improve bone formation and fusion, both in osteoporotic and nonosteoporotic animal, whereas spinal fusion is not enhanced in rats treated with Sr‐ßTCP + ADSCs. Thus, for conducting cells therapy in spinal surgery BMSCs still seems to be a better choice compared with ADSCs. Abstract : This study analyzed a strontium substituted ß‐tricalcium phosphate (Sr‐ßTCP) associated to syngeneic, unexpanded, and undifferentiated mesenchymal stem cells from bone marrow (BMSC) or adipose tissue (ADSC) as a new tissue engineering approach for spinal fusion procedures. Results suggest that addition of BMSCs to a Sr‐ßTCP improve bone formation and fusion, both in osteoporotic and nonosteoporotic animal, whereas spinal fusion is not enhanced in rats treated with Sr‐ßTCP + ADSCs. For conducting cells therapy in spinal surgery, BMSCs still seems to be a better choice compared with ADSCs.